Kebijakan Formulasi Pertanggungjawaban Pidana Terhadap Korporasi - Husni, Husni (Jurnal Ilmu Hukum Reusam, 2015)
According to criminal law regulation, the human is only the subject to be blamed in term of criminal action. A human can be as a guilty party of any criminal case. . However, this regulation has been abandoned by the Indonesian law system because of the perspective change that beside human, the corporate bodies are also as the subject of guilty party if the legal regulation is specificly determined by Legal Code in term of specific case. Therefore, based on the legal regulation, the corporate bodies are treated as equal as human in term of the subject of lawsuit so the , the rejection of prosecution toward corporate bodies based on Delinguere University’s doctrine- non potest has been changed by accepting the concept of functional doer. (fungtioneel daderschap). Although the constitution considers the corporate bodies as the subject of the lawsuit, the responsibility of criminal prosecution will be treated in a different ways from humans as a subjet of lawsuit. Although the corporate bodies can be prosecuted, the issue in implementing the case still remains due to the variation of the terminology used. Additionally, the other challenge is because the regulation implemented relating to corporate bodies’ lawsuit is still not determined specifically in criminal code. It is also insufficient and inconsistent prosecution regulation regarding to corporate body lawsuit.